Respiratory Problems among Workers of Udayapur Cement Factory in Eastern Nepal - Singh, Suman Bahadur; Gautam, Swotantra; Gautam, Rabin; Shrestha, Gambhir; Jha, Nilambar; Sharma, Sanjib Kumar (Journal of Nepal Health Research Council, 2019)
Background: There have been very limited studies regarding health of the cement factory workers in Nepal. This study aimed to find out the prevalence of health problems and the factors associated with respiratory symptoms among the workers of Udayapur cement factory. Methods: This is a cross-sectional study conducted from March to August 2015 in Udayapur cement factory in eastern Nepal. All the workers working in the factory more than a year were included in the study. Thedata was collected by using a semi-structured questionnaire consisting of socio-demographic characteristics,type of work, reported health problems, use of personal protective measures.Chi-square test was used to determine the association of respiratory symptoms with related variables. Results: A total of 295 workers were included in this study with mean age of 45.9 years (SD=7.7). Majority 279 (94.6%) were males. The most common health problems were musculoskeletal pain (55.6%) followed by eye problems (33.2%). Among them, 17(21.1%) reported that they had at least one respiratory problem and chest tightness while running/climbing and wheeze were the most common. A total of 233 participants (79%) used at least one form of personal protective equipment. Low education, longer duration of work and smoking were found to be positively associated with respiratory symptoms. Conclusions: Respiratory problems were high among the workers of the cement factory. Proper use of PPEs and dust control measures should be promoted among the workers. Keywords: Cement factory; eastern Nepal; occupational health; respiratory problems.